ANALISIS SIMBOL DALAM TRADISI LEDEK PADA MASYARAKAT DUSUN DOPLANG KECAMATAN JUMANTONO - Fitriana, Ema; Indria, Siany; Narendra Parahita, Bagas (Penerbit Lafadz Jaya, 2023)
This research analyzes the Ledek tradition as a ritual to ask for blessings and safety by the people of Dusun Doplang. One of the processions in this ritual, the community uses dancers called Ledek dancers as a symbol. The ritual is carried out once a year, on Friday Kliwon by the community, especially residents of Doplang Hamlet. By using qualitative research techniques, data were collected through documentation studies, observations, and in-depth interviews. Clifford Geertz's symbolic interpretation theory was used to examine the data. This study finds that the Ledek tradition still exists in Dusun Doplang and is still practiced by the community because it contains a number of symbolic elements and purposes that have an impact on the social structure of the Doplang hamlet community and encourage the Ledek tradition to continue. There are two symbolic reasons why the people of Dusun Doplang must continue to uphold the Ledek tradition: (1) As a symbol of friendship that strengthens togetherness, and (2) As a sign of tolerance, (3) The community needs to socialize. Then for its functions, namely as: (1) The function of safety, (2) The function of maintaining local wisdom, (3) The function of maintaining solidarity between communities.